Information and consumer demand for milk attributes: Are redundant labels an effective marketing strategy?. Issue 2 (23rd February 2021) - Ufer, Danielle; Ortega, David L.; Wolf, Christopher A.
Abstract: Product labels communicate the presence of valuable traits to consumers but, when a single label represents multiple traits, communication can be hindered by consumer misinformation. Redundant labels can address this problem by explicitly indicating included qualities within a comprehensive label. We use data from a field experiment on willingness to pay for redundant labels in the US organic fluid milk market when consumers are either uninformed or informed of the redundancy. Market share simulations demonstrate the market impacts and effectiveness of introducing a redundant label as a response strategy to recapture market share lost to increasingly prevalent individual labels.